Brotherhood and Sisterhood in the Chambers of Rhetoric in the Southern Low Countries - Van Bruaene, Anne-Laure (The sixteenth century journal, 2005)
The chambers of rhetoric in the Low Countries were amateur guilds or confraternities of laymen especially devoted to the composition of vernacular poetry and drama. The members were trained to perform not only in the semiprivate sphere of their chambers, but also in the public sphere, often in the context of civic festivals. This article asks if women had access to this formal literary culture that flourished in the urban middle class milieu of the Low Countries during the early modern period. It is argued that although some women produced rhetorician literature and a few of them did so successfully, women could never fully integrate into the culture of the chambers of rhetoric since this culture was based on a strong male group identity defined by social and religious codes.